Analisis kemampuan pemecahan masalah matematis siswa quitters ditinjau dari kemampuan metakognitif - Nurlaila Khasanah (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2021)
Tujuan penelitian ini adalah untuk mendeskripsikan kemampuan pemecahan masalah siswa dengan kategori quitter, adversity quotient (AQ) rendah, ditinjau dari kemampuan metakognitifnya. Kemampuan pemecahan masalah yang dimaksud di sini meliputi kemampuan dalam memeriksa kecukupan unsur, mencari alternatif penyelesaian, melaksanakan penyelesaian masalah, dan memeriksa kebenaran jawaban. Penelitian ini merupakan penelitian deskriptif kualitatif yang menggunakan teknik purposive sampling untuk memilih subjek penelitian. Subjek penelitian terdiri atas enam siswa kelas VIII di salah satu SMP negeri di Kota Jakarta Barat, di mana tiga siswa memiliki kemampuan metakognitif tinggi dan tiga siswa memiliki kemampuan metakognitif sedang. Data penelitian dikumpulkan dengan menggunakan angket AQ, angket metakognitif, tes kemampuan pemecahan masalah, dan wawancara. Data yang terkumpul kemudian dianalisis melalui proses reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Hasil penelitian ini menunjukkan bahwa siswa dengan kemampuan metakognitif tinggi cukup mampu dalam memeriksa kecukupan unsur, melaksanakan penyelesaian masalah, dan memeriksa kebenaran jawaban. Sementara itu, siswa dengan metakognitif sedang cukup mampu dalam memeriksa kecukupan unsur dan memeriksa kebenaran jawaban ketika terlibat dalam kegiatan pemecahan masalah matematika.Analysis of mathematical problem solving ability of quitter students based on metacognitive abilityThe purpose of this study was to describe the problem-solving abilities of quitter students, students with low level of adversity quotient (AQ), based on their metacognitive abilities. Students’ problem-solving abilities were examined based on their abilities in checking the required information to solve a problem, looking for alternative strategies to obtain a solution to the problem, solving the problem by following a problem-solving strategy, and evaluating the answer. This qualitative study applied purposive sampling technique to select subjects. The subjects were six eight graders at a public junior high school in West Jakarta which consisted of three students with high level of metacognitive ability and three students with moderate level of metacognitive ability. AQ questionnaire, metacognitive questionnaire, problem-solving test, and interview were used to collect data. The collected data were analyzed through data reduction, data display, and verification. The results indicated that students with high level of metacognitive ability were quite able to show their abilities in checking the required information to solve a problem, executing a problem-solving strategy to obtain the solution to the problem, and evaluating the answer. Meanwhile, students with moderate level of metacognitive ability were quite able to demonstrate their abilities in checking information needed to solve a problem and evaluating the answer.